Perception of Non-Muslim Community's Attitude to Islamic Banking in Kupang City, NTT - Kurniawan, Panji Rizki (Business Management, 2025)
The presence of Islamic banking in East Nusa Tenggara (NTT) continues to receive mixed responses from the public, particularly non-Muslims. This situation has led to various public perceptions of Islamic banking, which poses challenges for banks. This study aims to determine the perceptions of non-Muslim communities in East Nusa Tenggara (NTT) towards Islamic banking and the strategies offered to market Islamic banking products to non-Muslims in NTT. The method used in this study is qualitative research, with the type of research being: field research and the research approach is descriptive qualitative. The data sources in this study consist of primary data sources and secondary data sources. In order to collect data, data collection methods such as documentation and interviews were also used. The inductive cognitive method was used to conduct data analysis. The results of this study indicate that non-Muslim communities have different perspectives on Islamic banking. This is due to the lack of knowledge of non-Muslim communities in Kupang City regarding Islamic banking, and one of the factors that causes the community to have different views on Islamic banking is the education and socialization factors carried out by banks have not reached the community, which results in different perceptions among the community.